Analysis of Content-Based Higher Education Digital Media Business Development Needs - Prabayanti, Herma Retno (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
The development of technology and information affects various aspects of life, one of which is higher education. We are Social Related Digital Report (2023), states that of the 276.4 million Indonesians, 212.9 million Indonesians have used the internet in their daily activities and social media platforms, most frequently used are YouTube, Facebook, and WhatsApp. The multifunction of social media, in addition as media information, is as a medium to promotional activities. Universitas Negeri Surabaya, uses this opportunity to improve promotional strategies so that they have a positive impact on the university's business ecosystem. This study aims to determine the characteristics of the content needed by the audience when accessing university social media accounts. This research is a qualitative descriptive study, which analyzes the digital content needs of the unesa academic community using the Uses and Gratification theory. The results of this study found that the types of content that audiences are interested in include, (1) edutainment content; (2) content with attractive visuals; (3) content that involves audiences.